2016
DOI: 10.5935/abc.20160084
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study on Cardiotoxicity of Adjuvant Trastuzumab Therapy in Breast Cancer Patients

Abstract: BackgroundCardiotoxicity is an important side effect of trastuzumab therapy and cardiac surveillance is recommended.ObjectivesThe aim of our study was to prospectively assess baseline patients' characteristics, level of N-terminal pro-brain natriuretic peptide (NT-proBNP) and echocardiographic parameters as possible predictors of trastuzumab-related cardiac dysfunction.MethodsIn a prospective cohort study, clinical, echocardiographic and neurohumoral assessment was performed at baseline, after 4, 8 and 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…Previous studies have suggested that tamoxifen has a protective effect on cardiac function (31), whereas Herceptin treatment may be cardiotoxic (32). However, there was no such evidence of either tamoxifen-mediated cardiac protection or Herceptin-mediated cardiotoxicity in the study, in agreement with other previous studies (33,34). It may be the case that compared with the chemotherapy, both the protective effects of tamoxifen and the cardiotoxic effects of Herceptin were too weak to discern in these patients (35).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have suggested that tamoxifen has a protective effect on cardiac function (31), whereas Herceptin treatment may be cardiotoxic (32). However, there was no such evidence of either tamoxifen-mediated cardiac protection or Herceptin-mediated cardiotoxicity in the study, in agreement with other previous studies (33,34). It may be the case that compared with the chemotherapy, both the protective effects of tamoxifen and the cardiotoxic effects of Herceptin were too weak to discern in these patients (35).…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have demonstrated that strain changes precede EF changes in patients undergoing antineoplastic treatment. 14 , 16 , 18 - 21 However, no consensus has been reached regarding the specific cutoff point of that variable that should be used as a predictor of cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits HER2 shedding and metalloproteinase activity by decrease PTEN phosphorylation or AKT de‐phosphorylation to induce tumour cells death . Cardiotoxicity is a major reported side effect in trastuzumab‐treated patients and in some cases led to stop the antibody administration …”
Section: Anit‐her2 Mabs and Derivativesmentioning
confidence: 99%
“…[79] Cardiotoxicity is a major reported side effect in trastuzumab-treated patients and in some cases led to stop the antibody administration. [82,83] Pertuzumab (PERJETA)…”
Section: Trastuzumab (Herceptin)mentioning
confidence: 99%